ANALISIS FAKTOR – FAKTOR MOTIVASI KERJA PEGAWAI PADA PT.TASPEN (PERSERO) CABANG JAMBI - Muhamad Sidiq (Jurnal Dinamika Manajemen, 2015)
This study aims to describe the factors of employee motivation and to analyze the factors of employee motivation at PT.Taspen Jambi Branch. The method used to analyze the data in this study is descriptive analysis and data collection methods through literature, interviews and questionnaires. This study used a sample of 19 respondents and the aspects studied were the five factors of human needs, namely physiological needs, security needs, social needs, recognition needs and self-actualization needs. The results of this study indicate the work motivation of employees at PT. based on the employee's response to the questionnaire. Based on the results of this study, what can be suggested is that leaders in related agencies must understand the difficulties faced by their employees, because good leadership will lead to good motivation towards his subordinates, and all the resulting positive achievements must be maintained. The result of this research is the analysis of employee motivation factors.